294 Waiting for EURATOM 59/2013: Communicate and interact with users and patients on the perception of the ionizing radiation risk through an online survey. (December 2018) - Della Gala, G.; Chiesi, M.; Burani, A.; Rivetti, S.
Abstract : Purpose: The aim of this work was to undertake/experience an online survey to interact with user, patients and healthcare professionals. The survey had a twofold objective: first, to get users aware on the ongoing changes in Hospital-to-patient interaction due to the imminent transposition of the Directive EURATOM-59/2013, that is the communication of radiation dose data in X-ray medical exposures; therefore, to evaluate the perception of the radiation risk and to identify the participants' preferred way to communicate them the amount of radiation dose. Methods: The survey was developed on the website SurveyMonkey and published at the addresshttps://it.surveymonkey.com/r/NOSRadion . Users could access the survey by registering personal @mail address to a dedicated mailing-list, by visiting the Hospital website and by scanning a QR-code. No paper forms of the survey were proposed. The survey was developed to be brief and easy-to-read through three sections. In the first section personal data were recorded. In the second section, the personal feeling (interest and concern) with radiation risk connected to medical exposures was evaluated. In the last section, the preferred way to communicate dose to the patients was investigated by proposing several quantitative and qualitative options. Target recruiting group is established to 500 users. Results: A recap of the preliminary analysis based on the answers collected from the first 143 survey users (covered by around 70% by non-professionals) are shown in Table 1 and indicates a strong interest in the topic of radiation dose due to medical exposure, even if it was not coupled to great concern. Numerical quantification of the dose data was chosen by most of participants. Mean time for survey completion was about 5 min. Conclusions: Online survey showed to be an efficient and very low-cost way to interact with user/patients and a powerful tool to get qualitative information potentially useful to define management strategies. Survey outcomes are considered for future development of the Hospital environment.